EZ Enterprise / Mohd Danial... [et al.] - Rozaini, Mohd Danial; Harun, Mohd Noor Firdaus; Mohd Yusof, Anwar Ariff; Mat Yahya, Zulkifli; Azmi, Muhammad Hafizulfaka (2009)
This Business Plan is specifically designed on the purpose of obtaining a loan for developing a new venture in our area. To support our proposal, we had to do many researches regarding what we really want to implement on. In this case, we are to build on a project of electrical device and innovation. We selling a wireless switch which can replace any manual switch on the wall to remote switch (wireless). This Business Plan do contain lots of information on our entire plan that are the administrative plan, marketing plan, operational plan as well as the financial plan. It also consists wholly of data and information that has been collected and then analyzed with the proposed project in mind. Designing a Business Plan does bring hopes that we can actually get working on this project by receiving the source of capital that we are eager for. We had really stated on all necessities in the Business Plan just to have the attention of our evaluators. We do have the willingness to personally present or furnish any additional materials to facilitate better understanding of the proposed project.